UKURAN PERUSAHAAN SEBAGAI PEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS - Sari Mujiani; Wahyu Jum’atul (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This Purpose of this study aims to examine the effect of Profitability, Leverage and Liquidity on financial distress with firm size as Moderating in Transportation sub sector companies listed on the Indonesia Stock Exchange in 2015-2019. The population of this study includes all transportation sub-sector companies that have negative profits for 2 consecutive years between 2015-2019. The results of this study indicate that: (1) Profitability has a negative effect on the occurrence of financial distress. (2) Leverage has no effect on the occurrence of financial distress. (3) Liquidity has a negative effect on the occurrence of financial distress. (4) Profitability which is moderated through company size influences and strengthens financial distress. (5) Leverage moderated through company size does not affect financial distress. (6) Liquidity moderated through company size influences and strengthens financial distress